2009
DOI: 10.1080/09500340903398432
|View full text |Cite
|
Sign up to set email alerts
|

Epi-detected hybrid coherent Raman micro-spectroscopy

Abstract: We demonstrate efficient epi-detected coherent Raman micro-spectroscopy using a simple laser system based on a femtosecond mode-locked oscillator. In our experiment, the non-resonant background is eliminated by using a hybrid technique, which combines laser pulse shaping and timing with frequency-resolved detection, and is based on the different temporal behavior of parametric and nonparametric processes. We perform careful analysis to make sure the coherent Raman-resonant signal is generated in the backward d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In more detail, a linearly chirped and stretched (~1 ps) pump pulse generates a CARS signal only when overlapped in time with the Stokes pulse, offering spectral information according to the extent of the pump/probe time delay. As another approach to reduce the non-resonant background, researchers reported that if a tissue sample is detected in the epi-detection, non-resonant signals from tissue components as well as the solvent are almost completely eliminated [ 19 ]. Such epi-detection is possible when the sample is highly scattering.…”
Section: Introductionmentioning
confidence: 99%
“…In more detail, a linearly chirped and stretched (~1 ps) pump pulse generates a CARS signal only when overlapped in time with the Stokes pulse, offering spectral information according to the extent of the pump/probe time delay. As another approach to reduce the non-resonant background, researchers reported that if a tissue sample is detected in the epi-detection, non-resonant signals from tissue components as well as the solvent are almost completely eliminated [ 19 ]. Such epi-detection is possible when the sample is highly scattering.…”
Section: Introductionmentioning
confidence: 99%